2014
DOI: 10.1021/nl404032k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Motor Propelled Filaments Reveal Light-Guiding in Nanowire Arrays for Enhanced Biosensing

Abstract: Semiconductor nanowire arrays offer significant potential for biosensing applications with optical read-out due to their high surface area and due to the unique optical properties of one-dimensional materials. A challenge for optical read-out of analyte-binding to the nanowires is the need to efficiently collect and detect light from a three-dimensional volume. Here we show that light from fluorophores attached along several μm long vertical Al2O3 coated gallium phosphide nanowires couples into the wires, is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…This new approach facilitates biomicro/nano devices requiring advanced capabilities, such as instantaneous transformation of the track configuration, three dimensional delivery, active aiming, and chip-to-chip communication. With wire diameters down to submicrometer range this method is complementary, in terms of the dimension and flexibility, to other methods using nanometer scale wire-type guiding templates for molecular shuttles (Sikora et al, 2014;Byun et al, 2009;ten Sietoff et al, 2013). The glass wire-based approach presented here is, in general, applicable to different molecular motility systems, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This new approach facilitates biomicro/nano devices requiring advanced capabilities, such as instantaneous transformation of the track configuration, three dimensional delivery, active aiming, and chip-to-chip communication. With wire diameters down to submicrometer range this method is complementary, in terms of the dimension and flexibility, to other methods using nanometer scale wire-type guiding templates for molecular shuttles (Sikora et al, 2014;Byun et al, 2009;ten Sietoff et al, 2013). The glass wire-based approach presented here is, in general, applicable to different molecular motility systems, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The average speeds measured on the myosin-coated CNT (8.7 ± 3.5 μm/s; n = 32) were comparable to those measured on the glass surface in control experiments (6.0 ± 1.2 μm/s; n = 20), indicating that myosin motors retain their normal motile activity when adsorbed onto a CNT. Earlier studies with CNTs or semiconductor nanowires had reported sliding speeds far below the physiological speed-less than 20 % of that of kinesin (Sikora et al 2014) and~42 % of that of myosin (Siethoff et al 2014). The normal level of motility shown by the CNT-adsorbed myosin molecule in this system (Inoue et al 2015) is the first demonstration that a single CNT can be used as a platform to evaluate this protein's normal function as a myosin motor.…”
Section: Observation Of Motor Function On a Single Cntmentioning
confidence: 78%
“…Tsuchiya et al (2010) constructed a container transport system, powered by myosin-VI that can move CNTs along an intracellular track of actin filaments. Multi-walled CNTs and semiconductor nanowires can be used as a onedimensional (1-D) track for the myosin-based sliding of actin filaments (Siethoff et al 2014) and the kinesin-based sliding of microtubules (Sikora et al 2014). Motor proteins are compatible with CNTs and produce activity that is easily observed, such as actin-binding kinetics and enzyme-based motile activity.…”
Section: Motor Proteinsmentioning
confidence: 99%
“…Semiconductor nanowire arrays are used in a growing number of bio-applications ranging from biosensing [1][2][3][4][5][6][7][8][9][10][11][12][13], tuning cellular growth and adhesion [14][15][16][17][18][19][20][21], to transfecting cells [22,23]. A particularly promising application would consist of using nanowires to improve current neural implants, which are limited by the formation of a scar around the implant electrodes [24].…”
Section: Introductionmentioning
confidence: 99%